THE OBSTACLES IN LEARNING VOCABULARY OF EFL STUDENTS - Nisrina Lutfiyah; Nuraeningsih Nuraeningsih; Rusiana Rusiana (Universitas Muria Kudus, 2022)
There are many problems faced by students which prevent them from improving their English skills and abilities. One of the most common is their vocabulary mastery. This study aimed to figure out what obstacles they encountered in learning vocabulary and what strategies they used to solve their problems. It is a survey and the respondents were 30 students of second semester students of Universitas Muria Kudus. Questionnaire was used as the instrument to obtain data. The study revealed that there were several obstacles in learning vocabulary, i.e., difficulty in distinguishing how to spell and pronounce English words correctly, difficulty in developing their vocabulary skills and difficulty in using vocabulary correctly and difficulty in understanding the connotation. To solve the problems, the students do some strategies, namely (1) dictionary strategy and memorization (2) peer practice (3) listening to music or watching English videos (4) share and discussion with friends, and (5) additional individual class.